The Utility of Homemade ELISA Based Outer Membrane Proteins (OMP) of Salmonella Typhi in Diagnosis of Chronic Typhoid Carrier - Thanaa R. Abdulrahman (Journal of Global Pharma Technology, 2018)
Typhoid fever is an extreme multi-systemic infection, constitutional symptoms is a major findings with classic prolonged fever. The simplicity, sensitivity, specificity and cost effective of diagnostic test which will be used in diagnosis of typhoid fever in human carriers, would give a compelling apparatus in controlling and preventing typhoid. The aims of this investigation were to determine the proportion of typhoid carriers by using homemade ELISA test based on OMP extraction. This study included fifty febrile patients and thirty age and sex matched apparently healthy individual as control with no history of immunization in the recent past, they were 24 (48%) males and 26 (52%) females, the age was ranged between 18-40 year with mean (33.6) .Blood and stool samples were collected from each participant and these samples underwent culturing on special media, after OMPs extraction from Salmonella typhi. Sandwich homemade ELISA were developed for detection of anti typhoid IgG and IgM using crud OMPS as antigen .The results showed that 18 (36.0%) out of 50 patients were stool culture positive, while blood culture results confirmed typhoid fever in 7 (14.0%) patients. Out of 50 serum samples were tested by homemade ELISA kit, which prepared in this study for IgG /IgM detection, there were 35(70.0%) IgG positive and only 8 (16.0%) was IgM positive. For IgG and/or IgM, as tested by ELISA positive results in accordance with stool and blood culture assays .For stool positive culture, IgG ELISA (26%) 13/50, showed positive results, while IgM (6.0 %) 3/50.Keywords: Salmonella typhi, Outer membrane protein, Homemade ELISA, Anti-typhoid antibodies, Roc test.